Poor prognosis associated with TERT gene alterations in meningioma is independent of the WHO classification: an individual patient data meta-analysis - Mirian, Christian; Sahm, Felix (Journal of neurology, neurosurgery, and psychiatry, 2020)
Background TERT gene alterations (TERT-alt) have been linked to increased risk of recurrence in meningiomas, whereas the association to mortality largely remain incompletely investigated. As incongruence between clinical course and WHO grade exists, reliable biomarkers have been sought. - Methods We applied the Preferred Reporting Items for Systematic Review and Meta-Analyses of individual participant data Statement. We compiled data from eight studies and allocated patients to TERT-alt (n=59) or TERT promoter wild-type (TERTp-wt; n=618). We compared the two groups stratified for WHO grades as: incidence rates, survival probabilities and cumulative recurrences. We estimated the effects of WHO grade, age at diagnosis and sex as HRs. - Results TERT-alt occurred in 4.7%, 7.9% and 15.4% of WHO-I/WHO-II/WHO-III meningiomas, respectively. The median recurrence-free survival was 14 months for all TERT-alt patients versus 101 months for all TERTp-wt patients. The HR for TERT-alt was 3.74 in reference to TERTp-wt. For all TERT-alt patients versus all TERTp-wt patients, the median overall survival was 58 months and 160 months, respectively. The HR for TERT-alt was 2.77 compared with TERTp-wt. TERT-alt affected prognosis independent of WHO grades. Particularly, the recurrence rate was 4.8 times higher in WHO-I/-II TERT-alt patients compared with WHO-III TERTp-wt patients. The mortality rate was 2.7 times higher in the WHO-I and WHO-II TERT-alt patients compared with WHO-III TERTp-wt patients. - Conclusions TERT-alt is an important biomarker for significantly higher risk of recurrence and death in meningiomas. TERT-alt should be managed and surveilled aggressively. We propose that TERT-alt analysis should be implemented as a routine diagnostic test in meningioma and integrated into the WHO classification. - Trial registration number PROSPERO: CRD42018110566.
Gesehen am 24.06.2020